Social Evaluation of Individual Welfare Effects from Income Taxation Empirical Evidence Based on Italian Data for Married Couples - Rolf Aaberge; Ugo Colombino (Statistics Norway, Research Department, 1998)
This paper discusses methodological principles for social evaluation of tax systems and tax reforms when concern is primarily turned to who gains and who loses. The discussion is followed by an empirical analysis based on Italian household data. Using a household microeconometric labor supply model we have simulated behavioral responses and welfare gains and losses for married couples resulting from replacing the Italian tax system as of 1993 by proportional taxation.
Keywords: D19; D69; J22; 330; Labor supply; taxation; welfare gains and losses; social welfare